The Level of Social Engagement in the Success of the Elderly Posyandu Program in Indonesia - Hidayati, Nurul; Sudarmo, Sudarmo; Dwi Wahyunengseh, Rutiana (Riviera Publishing, 2023)
The elderly population is an inevitable stage of life that everyone will experience. In Indonesia, the health issues faced by the elderly require the attention and readiness of society, experts, and the government. This research aims to analyze the level of social engagement in the success of the elderly Posyandu program in Indonesia. Qualitative and library research methods are employed. The narrative method is used to analyze the literature, with secondary data collected from databases such as Scientific Direct and Scholar. Results: Initially, 2700 research studies and articles were identified from the databases. After screening for publication year, duplicate titles, and abstracts, 10 research studies were selected. The criteria for the articles or journals focused on social engagement, elderly, and healthcare services. The findings of the research highlight three main points: (1) supporting factors in implementing the elderly Posyandu program, such as community outreach and ensuring adequate facilities, (2) involvement of various services including preventive, curative, rehabilitative, and promotive programs, and (3) the importance of social engagement, which involves active participation of the elderly and receiving emotional and social support from family and the community. Social engagement programs for elderly Posyandu in major cities have shown positive outcomes. Active involvement of the elderly, support from family and the community, improved accessibility, information and education, and emotional support are key factors contributing to the program's success. Based on these successful outcomes, this study recommends the participation of Posyandu in social engagement program activities in other major cities.